Assessment of Factors Affecting Building Construction Workers When Working at Height - Timothy Adu Gyamfi; Edward John Cobbina; Millicent Owusu-Kumi; Emmanuel Yaw Frempong – Jnr (Journal of Construction Project Management and Innovation)
Falls from heights are the leading cause of fatal incidents in the global construction industry. Despite several efforts to mitigate this risk, falls from heights remain the most frequent type of accident in the construction sector. Given this impact, researchers find it critical to assess the factors influencing construction workers when working at height. To validate the study's objectives, 97 employees with expertise in working at height were sampled. A self-administered questionnaire was used to collect responses from the participants. The study employed both simple random and purposive sampling techniques. Data analyses were conducted using Excel and SPSS. The study identified four key factors affecting construction workers when working at height: personnel factors, safety checks and safety signs factors, personal protective equipment factors, and overloading factors. The findings suggest that, to protect employees' health and safety, contractors should implement programmes tailored to height-related work at construction sites to raise awareness of the associated risks. Additionally, employers must ensure that workers wear appropriate personal protective equipment (PPE) in compliance with workplace health and safety policies for working at height. This research is limited to the building construction industry in the Akuapem South Municipality and Ga South Municipality, located in Ghana's Eastern and Greater Accra Regions. The findings are relevant to the building construction industry, particularly in Ghana, where studies on working at height are limited. This paper contributes to the existing body of literature on working at height in the Ghanaian building construction sector.